Volcanism and Mass Extinction - Font, Eric; Bond, David P.G. (Academic Press, 2020)
During the Phanerozoic, life on Earth experienced several mass extinctions, each associated with major climatic and environmental changes. The cause(s) of the biotic crises have been debated for decades but recent improvements in radioisotopic dating have revealed a close temporal link between large igneous province (LIP) activity and extinction events recorded in marine and terrestrial sedimentary rocks. This inferred causal relationship has been strengthened by the emergence of the mercury (Hg) proxy as evidence for massive volcanism in sedimentary records, as well as paleotemperatures calculated from the oxygen isotopic composition of various fossil shells and terrestrial fossil plants and paleosol carbonate. Current challenges focus on understanding the climatic and environmental changes induced by LIPs and resolving the kill mechanisms responsible for mass extinctions. This article examines the link between LIPs and major Phanerozoic mass extinction events. We focus on the two best known crises: the end-Cretaceous mass extinction, where bolide impact and eruptions in the Deccan Traps famously wiped out the (nonavian) dinosaurs; and the end-Permian mass extinction—the greatest crisis in Earth's history. We conclude with a brief overview of the other major crises of the Phanerozoic.